The risk of venous and arterial thrombosis in hyperhomocysteinaemia is low and mainly depends on concomitant thrombophilic defects - Lijfering, Willem M.; Coppens, Michiel; van de Poel, Marlène H. W.; Middeldorp, Saskia; Hamulyák, Karly; Bank, Ivan; Veeger, Nic J. G. M.; Prins, Martin H.; Büller, Harry R.; van der Meer, Jan (Thrombosis and Haemostasis, 2007)
As homocysteine-lowering treatment has not reduced the risk of recurrent thrombosis in recent clinical trials, we hypothesized that mild hyperhomocysteinaemia is an epiphenomenon or associated with a low absolute risk of thrombosis. In this retrospective study, we enrolled 478 evaluable first-degree relatives of consecutive patients with venous thrombosis or premature atherosclerosis, and hyperhomocysteinemia. Absolute risks of thrombosis and effects of concomitant thrombophilic defects were compared. Relative risks were adjusted for clustering in families, age, sex, and atherosclerotic risk factors, where appropriate. Annual incidence of venous thrombosis was 0.16% (95% confidence interval [CI], 0.08–0.30) in hyperhomocysteinemic relatives versus 0.11% (CI, 0.05–0.20) in normohomocysteinemic relatives; adjusted relative risk 1.6 (CI, 0.6–4.5). Annual incidences of arterial thrombosis were 0.34% (CI, 0.21–0.52) and 0.24% (CI, 0.15–0.37) in hyperhomocysteinemic and normohomocysteinemic relatives, respectively; adjusted relative risk 1.5 (CI, 0.6–3.5). Concomitance of multiple thrombophilic risk factors increased the risk of venous thrombosis in hyperhomocysteinemic relatives 20 fold, but a comparable effect was demonstrated in normohomocysteinemic relatives. We conclude that hyperhomocysteinaemia is associated with a low absolute risk of venous and arterial thrombosis. Concomitant thrombophilic defects are probably main determinants on the risk of venous thrombosis, rather than hyperhomocysteinaemia itself.
Keywords: Clinical studies; risk factors; venous thrombosis; arterial thrombosis; thrombophilia